Preliminary investigation of the prevalence and implantation potential of abnormal embryonic phenotypes assessed using time-lapse imaging. Issue 5 (May 2017) - Barrie, Amy; Homburg, Roy; McDowell, Garry; Brown, Jeremy; Kingsland, Charles; Troup, Stephen
Abstract: This retrospective, single site observational study aimed to delineate five abnormal embryonic developmental phenotypes, assessing their prevalence, development potential and suitability for inclusion in embryo selection models for IVF. In total, 15, 819 embryos from 4559 treatment cycles cultured in EmbryoScope® incubators between January 2014 and January 2016 were included. Time-lapse images were assessed retrospectively for five abnormal embryo phenotypes: direct cleavage, reverse cleavage, absent cleavage, chaotic cleavage and cell lysis. The prevalence of each abnormal phenotype was assessed. Final embryo disposition, embryo quality and implantation rate were determined and compared with a control embryo cohort. The collective prevalence for the five abnormal phenotypes was 11.4%; chaotic cleavage and direct cleavage together constituted 9.7%. Implantation rates were 17.4%, 0%, 25%, 2.1% and 0% for direct, reverse, absent, chaotic cleavage and cell lysis, respectively. The overall implantation rate for all abnormal embryos with known implantation status was significantly lower compared with the control population (6.9% versus 38.7%, P < 0.0001). The proportion of good quality embryos in each category of abnormal cleavage remained below 25%. Embryos exhibiting an abnormal phenotype may have reduced developmental capability, manifested in both embryo quality and implantation potential, when compared with embryos of normal phenotype.